If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x = 10 + -5(x + -7) Reorder the terms: 10x = 10 + -5(-7 + x) 10x = 10 + (-7 * -5 + x * -5) 10x = 10 + (35 + -5x) Combine like terms: 10 + 35 = 45 10x = 45 + -5x Solving 10x = 45 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. 10x + 5x = 45 + -5x + 5x Combine like terms: 10x + 5x = 15x 15x = 45 + -5x + 5x Combine like terms: -5x + 5x = 0 15x = 45 + 0 15x = 45 Divide each side by '15'. x = 3 Simplifying x = 3
| 8+5n=7(n+2) | | x+2x-6=-12+2x | | (5x^2)-6x-6=0 | | -5v+2v=9 | | (8-7x)(7x+8)= | | 3x^2-3x/9 | | 8a-24=2(a+3) | | 2(11.75+.75y)-1=y | | 7x+6xy=8yx+11y | | -7*(3-a)=8*(5-2a) | | 0=3x^2+4x-1 | | y+10x=e | | y=80+0.8y | | 2x*lnx+2=0 | | 2x-3y-3=0 | | 80+0.8y=200 | | (4x+3)(x+2)=(3x)(2x+2) | | v-2-5v=6 | | -1+-2=-25+8 | | 6*12=4*(6+3b) | | 2x^2-6x-15=0 | | 4x+17=8x+37 | | y^2-6x=0 | | (4-w)(4w-1)=0 | | 3y-10=2y-4 | | 8x+10=11x-23 | | -2+9y=-4 | | 26-5x=10-9x | | 7-(2+2r)=20 | | 6x+13=-32-3x | | -9/25=p/125 | | 11-2(4-x)=3x-1(5-2x) |